Game-Based Sharing in Problem-Based Learning: Enjoyable Learning Strategies to Improve Student Collaboration - Yonna Divanka Yuanvanelli; Yayuk Mulyati; Erti Hamimi (Universitas Syiah Kuala, in collaboration with the Perkumpulan Pendidik IPA Indonesia (PPII), (MoU), 2026)
Problem-based learning (PBL) is widely applied to improve 21st-century skills, including collaboration. However, few studies integrate enjoyable learning to encourage students' active interaction in collaboration. The purpose of this study is to analyze the effectiveness of game-based sharing integration in PBL as an enjoyable learning strategy to improve students' collaboration skills. A quasi-experimental approach with a posttest-only non-equivalent control group design was used. The sample consisted of grade VIII students in a Malang City junior high school selected through purposive sampling. The experimental class applied game-based sharing-based PBL (GS-PBL), while the control class used PBL without game-based sharing. Results showed that integrating game-based sharing in PBL significantly improved students' collaboration skills. T-test analysis indicated significant differences between the experimental and control classes, with p-values of 0.000 (observers) and 0.001 (peers) (p < 0.05). Cohen's effect size analysis showed a large effect on collaboration skills (1.156 by observers and 0.92 by peers). Based on five indicators of collaboration, the experimental class scored higher than the control class. Indicators needing improvement in the control class include active participation, productive work, and flexibility and compromise. Thus, GS-PBL is more recommended for creating interactive, enjoyable learning experiences